2020
DOI: 10.3390/jcm9124020
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Patterns of BECN1, LAMP2, and PINK1 Genes in Colorectal Cancer Are Potentially Regulated by Micrornas and CpG Islands: An In Silico Study

Abstract: Background: Autophagy plays a dual role of tumor suppression and tumor promotion in colorectal cancer. The study aimed to find those microRNAs (miRNAs) important in BECN1, LAMP2, and PINK1 regulation and to determine the possible role of the epigenetic changes in examined colorectal cancer using an in silico approach. Methods: A total of 44 pairs of surgically removed tumors at clinical stages I‒IV and healthy samples (marginal tissues) from patients’ guts were analyzed. Analysis of the obtained results was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Our findings were consistent with those of previous reports and showed that LAMP2 could serve as a biomarker to promote the development and progression of ESCA ( 40 ). Similarly, studies have confirmed that LAMP2 can promote cell migration and invasion in some types of cancers, including LUAD ( 13 ), LIHC ( 14 ), COAD ( 15 ), and PRAD ( 16 , 17 ). However, no previous studies have evaluated the significance of LAMP2 on a pan-cancer basis.…”
Section: Discussionmentioning
confidence: 78%
“…Our findings were consistent with those of previous reports and showed that LAMP2 could serve as a biomarker to promote the development and progression of ESCA ( 40 ). Similarly, studies have confirmed that LAMP2 can promote cell migration and invasion in some types of cancers, including LUAD ( 13 ), LIHC ( 14 ), COAD ( 15 ), and PRAD ( 16 , 17 ). However, no previous studies have evaluated the significance of LAMP2 on a pan-cancer basis.…”
Section: Discussionmentioning
confidence: 78%
“…These studies suggested that mutations in ATG genes may contribute to cancer development by deregulating the autophagy process [ 40 ]. Others have identified changes in the expression and/or epigenetic regulation of ATG genes, such as: PINK1 (involved in mitophagy) [ 33 ], BECN1 (involved in macroautophagy) and LAMP2 (involved in chaperone-dependent autophagy) depending on the stage of CRC [ 41 ]. This recent study showed results on the role of miRNAs regulating three of the ATG genes mentioned above, and these are BECN1 -49 mRNA, LAMP2 -62 mRNA and PINK1 -6 mRNA.…”
Section: Autophagy In Colorectal Cancer—clinical Implicationsmentioning
confidence: 99%
“…This recent study showed results on the role of miRNAs regulating three of the ATG genes mentioned above, and these are BECN1 -49 mRNA, LAMP2 -62 mRNA and PINK1 -6 mRNA. Promoter regions containing at least one CpG region have been detected and described [ 41 ].…”
Section: Autophagy In Colorectal Cancer—clinical Implicationsmentioning
confidence: 99%
“…Autophagy is a doubleedged sword. It can be used as a tumour suppressor that selectively inhibits protein degradation and destroys organelles, and it can also be used as a cell survival promoter that promotes tumour growth [8][9][10]. Studies have shown that autophagy-related genes are frequently mutated in endometrial cancer, and that autophagy disorders are closely related to the occurrence and development of endometrial cancer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%